Growth, bank credit, and inflation in Mexico: Evidence from an ARDL-bounds testing approach - Miguel Ángel Tinoco-Zerme\~no; Francisco Venegas-Martínez; Víctor Hugo Torres-Preciado (Latin American Economic Review, 2014)
This paper explores the long-run effects of inflation on the dynamics of private sector bank credit and economic growth in Mexico over the period 1969 - 2011. With an ARDL-type model, the statistical results suggest that the availability of private sector bank credit in the economy exerts a positive impact on real GDP. In addition, inflation rates have contributed negatively to the increase in private credit, liquid liabilities, and financial development. A key outcome is that one percent increase in inflation is associated with a 0.07 % fall in long-run real rate of output through its effect on bank credit to the private sector. Another crucial finding is that policies of financial liberalization have helped stimulate economic growth. Reinforcing the literature on finance and growth, this study reaffirms that inflation rates are detrimental to long-run financial development and economic growth.
Keywords: E31; G21; E44; O4; C22; 330; Inflation; Private sector bank credit; Financial development; Growth